(untitled) (Global Journal of Management and Business Research, 2019)
This study examined the effect of ethical and professional values based on the socioeconomic factors affecting banking operations of deposit money banks in Nigeria. Prior studies have not dwelt or investigated extensively on ethical and professional practices by banks especially in developing world like Nigeria. Hence, there is the need to evaluate the effectiveness, enforcement and compliance by banks of the codes of ethics and professionalism for the banking industry in Nigeria. Mixed research design method employed with the aid of primary data collected through close ended structured questionnaire from 200 respondents purposively selected from the commercial deposit money banks and three core regulatory institutions for the industry. Both descriptive and inferential statistics were employed to analyze the data and the hypothesis tested with Pw and Kendall’s Tau Correlation Coefficients. Findings revealed that the level of ethical and professional competence have not improved as expected.